Implementasi Pendidikan Humanis Islami Dalam Pemulihan Trauma Pascabencana Banjir Di Aceh - Cita Ayni Putri Silalahi; Alistraja D. Silalahi; Herlina Hanum Harahap; Nurul Azmi Saragih; Muthmainnatul Husna (CV. BAROKAH PUBLISHER, 2026)
This community service activity aims to help children recover from post-flood trauma through the implementation of Islamic humanistic education at Sang Juara Tutoring Institute in Aceh Tamiang. The implementation method was carried out through the stages of preparation, implementation, and mentoring using lecture methods, question-and-answer sessions, and religious approaches based on Islamic values. The results of the activity showed a decrease in students’ anxiety and fear, increased learning motivation, self-confidence, and better social interaction. In addition, this activity also instilled the values of patience, trust in Allah (tawakkal), and optimism in students after the disaster. Therefore, Islamic humanistic education proved effective in helping children recover from post-flood trauma.